Has European Union legislation to reduce exposure to chromate in cement been effective in reducing the incidence of allergic contact dermatitis attributed to chromate in the UK?. Issue 2 (17th August 2011) - Stocks, S J; McNamee, R; Turner, S; Carder, M; Agius, R M
Abstract : Objective: Hexavalent chromate (chromate) in cement is a well-recognised cause of allergic contact dermatitis (ACD). Consequently in January 2005, following European Union legislation (EU Directive 2003/53/EC), the use or supply of cement containing >2 ppm of chromate was prohibited in the UK (COSHH 2004). This analysis of work-related ill-health surveillance aims to evaluate the effectiveness of this legislation. Method: Changes in the incidence of work-related ACD cases returned to The Health and Occupation Reporting network by dermatologists were analysed taking in to account attribution to chromate and occupation. Results: There was a significant decline in the incidence of both ACD attributed to chromate (incidence rate ratio 0.48, 95% CI 0.36 to 0.64) and ACD not-attributed chromate (0.76, 95% CI 0.69 to 0.85) between the time period preceding the EU legislation (2002–2004) and the postlegislation period (2005–2009). However, the decline in ACD attributed to chromate was significantly greater (p=0.006). This decline was further increased in workers potentially exposed to cement (incidence rate ratio 0.37, p=0.001). The majority of the decline in incidence occurred during 2005. Conclusion: The timing of this significant decline in the UK incidence of chromate attributed ACD, and the greater decline in workers potentially exposed to cement strongly suggests that the EU Directive2003/53/EC was successful in reducing exposure to chromate in cement in the UK.